2003
DOI: 10.1093/pasj/55.2.467
|View full text |Cite
|
Sign up to set email alerts
|

Non-Linear Resonance in Nearly Geodesic Motion in Low-Mass X-Ray Binaries

Abstract: We have explored the ideas that parametric resonance affects nearly geodesic motion around a black hole or a neutron star, and that it may be relevant to the high frequency (twin) quasi-periodic oscillations occurring in some low-mass X-ray binaries. We have assumed the particles or fluid elements of an accretion disc to be subject to an isotropic perturbation of a hypothetical but rather general form. We find that the parametric resonance is indeed excited close to the radius where epicyclic frequencies of ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
207
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(221 citation statements)
references
References 21 publications
13
207
1
Order By: Relevance
“…Further, Rezzolla et al (2003a,b) studied small perturbations of an accretion torus orbiting close to the black hole and modeled the observed high QPO frequencies with basic p-modes of relativistic tori. They showed that these modes behave as sound waves trapped in the torus with eigenfrequencies appearing in the sequence 2:3:4:... Abramowicz et al (2003) also proposed that the observed rational ratios of frequencies may be due to the strong gravity of the compact object and a non-linear resonance between radial and vertical oscillations in accretion disks.…”
Section: Flrs In the Presence Of Ambient Flow (Along The Magnetosphermentioning
confidence: 99%
“…Further, Rezzolla et al (2003a,b) studied small perturbations of an accretion torus orbiting close to the black hole and modeled the observed high QPO frequencies with basic p-modes of relativistic tori. They showed that these modes behave as sound waves trapped in the torus with eigenfrequencies appearing in the sequence 2:3:4:... Abramowicz et al (2003) also proposed that the observed rational ratios of frequencies may be due to the strong gravity of the compact object and a non-linear resonance between radial and vertical oscillations in accretion disks.…”
Section: Flrs In the Presence Of Ambient Flow (Along The Magnetosphermentioning
confidence: 99%
“…They are constants, which depend on r 0 , the distance of the unperturbed orbit from the centre. In previous studies these non-linear differential equations have been integrated numerically (Abramowicz et al 2003) and analyzed through a perturbative method. These coupled harmonic oscillators display internal non-linear resonance, the strongest one occurs when ω θ :ω r = 3:2 and the observed frequencies are close (but not equal) to the epicyclic ones.…”
Section: Dynamics Of a Test Particlementioning
confidence: 99%
“…However these epicyclic oscillations would not be detectable without any source of energy to make their amplitudes grow. In Abramowicz et al (2003) and Rebusco (2004) this source of energy was inserted by introducing a parameter α. The effect of forcing (e.g., due to the neutron star spin), and its potential to produce new (external) resonances, have been addressed recently (e.g.…”
Section: Additional Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the expected links with the orbital motion, most work about kHz QPOs focus on the explanation for the nature of these signals (e.g. Miller, Lamb & Psaltis 1998;Stella & Vietri 1998Kluzniak & Abramowicz 2001;Abramowicz et al 2003;Zhang 2004). The kHz QPOs often arise as simultaneous twin peaks (upper ν 2 and lower ν 1 frequency) with frequencies changing over time.…”
Section: Introductionmentioning
confidence: 99%